2010
DOI: 10.1111/j.1365-2850.2009.01506.x
|View full text |Cite
|
Sign up to set email alerts
|

The experience and consequences of people with mental health problems, the impact of stigma upon people with schizophrenia: a way forward

Abstract: The aim of this literature review is to explore stigma as experienced by individuals with mental health problems, focusing primarily on schizophrenia. The concept of stigma has been examined. Service users' reports of their experiences of stigma have been outlined. The role of the media, public perceptions and the role of the nurses and mental health services have been discussed. Proposals have been suggested to address stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 52 publications
2
33
0
2
Order By: Relevance
“…Diagnostic overshadowing, whereby the primary diagnosis of a mental illness distracts from the person's physical health problem being recognized, is particularly problematic (Jones et al 2008). While toolkits have been developed to enable practitioners to overcome some of the barriers to helping people with SMI access appropriate physical health care (Phelan et al 2004), it has been suggested that problems remain, at least in part due to the inequitable distribution of resources resulting from social discrimination around mental illness (Harrison & Gill 2010). This can be through cultural norms, such as professionals' acceptance of smoking behaviour (Johnson et al 2010;Ratschen et al 2011), and indistinct roles and lack of clarity of key responsibilities (Arvidsson & Hultsjo 2009).…”
Section: Voice Of Reasonmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic overshadowing, whereby the primary diagnosis of a mental illness distracts from the person's physical health problem being recognized, is particularly problematic (Jones et al 2008). While toolkits have been developed to enable practitioners to overcome some of the barriers to helping people with SMI access appropriate physical health care (Phelan et al 2004), it has been suggested that problems remain, at least in part due to the inequitable distribution of resources resulting from social discrimination around mental illness (Harrison & Gill 2010). This can be through cultural norms, such as professionals' acceptance of smoking behaviour (Johnson et al 2010;Ratschen et al 2011), and indistinct roles and lack of clarity of key responsibilities (Arvidsson & Hultsjo 2009).…”
Section: Voice Of Reasonmentioning
confidence: 99%
“…This is interesting when explored against the backcloth of a growing call in the UK to harness patient experience knowledge (Staley 2009;Stickley 2006;Warne & McAndrew 2007). Indeed, it has been suggested that an appropriate starting place to address the power imbalance between service user and professional may be for professionals to relinquish some of their power by acknowledging the centrality of the patients' expert knowledge in their life trajectory and the subsequent sharing of expertise (Harrison & Gill 2010;Warne & McAndrew 2007). Robson and Gray (2007) identified similar problems in their synthesis of epidemiological evidence and the possible causes of poor physical health, from a professional viewpoint, experienced by people with SMI.…”
Section: The Interpersonalmentioning
confidence: 99%
“…Stigma has been used to study the association of negative characteristics on issues such as race [12], mental health [13], HIV/AIDS [14], discrimination [15], and social class [16]. Equally important are its profound effects such as undermining self-esteem and self-efficacy [17], suffering unemployment [18] and the reduction of life chances [19].…”
Section: Stigmamentioning
confidence: 99%
“…8 The current research aimed to contribute to existing literature and inform the practice of giving the diagnosis of schizophrenia by exploring individuals’ subjective experiences of receiving a diagnosis of schizophrenia and stigma relating to the diagnostic label.…”
mentioning
confidence: 99%